Influence of rhizopheric bacteria on germination and initial growth of Sporobolus cryptandrus (Torr.) A. Gray - B?cquer, C. J.; Salas, Beatr?z; Slaski, J.; Archambault, D.; Anya, A. (Cuban Journal of Agricultural Science, 2013)
In order to assess the effect of rhizobacteria strains on seeds of Sporobolus cryptandrus, a standard methodology was applied for the inocula preparation and seeds inoculation, according to that recommended in the international literature. A completely randomized experimental design with ten treatments and ten repetitions was used. The percent of germination, germination increase compared with the control, longitude of the radicle and plumule were assessed. In the germination, the treatments with the strains MSDJ865 (100 %) and ATCC9039 (100 %) had values higher than the rest, with increase of 40 % in respect to the control. In the plumule longitude, the treatments with ATCC9039 (19.10 mm), ATCC7486 (19.22 mm) and ORS534 (19.11 mm) were superior to the control. In the radicle longitude, the treatments HA1 (46.10 mm), ORS534 (45.33 mm) and ATCC9039 (44.30 mm) were superior to the control and to the majority of the treatments. It is concluded that the most outstanding strains in the variables studied were ATCC9039, ORS534, MSDJ865 and HA1. The longitude of the radicle was the variable with highest contrast of statistical values caused by inoculation. The strains belonging to Bradyrhizobium sp. showed different effects on the variables studied, in spite of their common taxonomic origin. Greenhouse tests with the strains ATCC9039, ORS534, MSDJ865 and HA1, are recommended, as well as similar studies in other meadow grasses. Key words: inoculation, rhizobacteria, meadow grasses.